Molecular Characterization and Expression Analysis of a Novel Glutaredoxin 3 Gene in Pacific White Shrimp (Litopenaeus vannamei) - Zheng, Peihua; Zhang, Xiuxia; Wang, Dongmei; Li, Juntao; Zhang, Zelong; Lu, Yaopeng; Xian, Jianan; Wang, Anli; Wang, Lei (Frontiers in Marine Science, 2021)
Glutaredoxins (Grxs), small heat-stable oxidoreductases, are key members of thioredoxin (Trx) superfamily. Recently, an emerging subclass of Grxs with one cysteine residue in the active site was found in shrimps. However, molecular functions of glutaredoxin-related proteins in decapods were rarely reported. In this study, a novel full-length Grx 3 (LvGrx 3) complementary DNA (cDNA) was identified in Pacific white shrimp (Litopenaeus vannamei), which had a 975 bp open reading frame (ORF) encoding a polypeptide of 324 amino acids. Nucleic acid sequence of Pacific white shrimp glutaredoxin 3 (LvGrx 3) showed 99.59% identity with genomic DNA (gDNA) sequence and 63.49% coverage. Sequence alignment showed that the amino acid sequence of LvGrx 3 shared 97% identity with black tiger shrimp (Penaeus monodon) Grx 3 and 62% identity with amphipod (Hyalella azteca) Grx 3. LvGrx 3 showed higher expression in intestine, gill and hepatopancreas and lower expression in epithelium and abdominal nerve. In response to ammonia-N stress, LvGrx 3 was significantly up-regulated in both hepatopancreas and gill, and the peak value appeared after 24 h exposure. After lipopolysaccharide (LPS) injection, expression levels of LvGrx 3 in hepatopancreas were increased in the middle stage, and LvGrx 3 in gill was up-regulated in the middle and later periods (24 and 48 h). These results indicate that LvGrx 3 can participate in immune responses against ammonia-N stress and pathogen infection. However, RNA interference (RNAi) assay showed that LvGrx 3 silencing in ammonia-N challenged shrimp could significantly induce the gene expression of antioxidant enzymes and aggravate the oxidative damage of protein and lipid. These results suggest that LvGrx 3 is involved in regulating the antioxidant system and plays a vital role in defense responses against environmental stress.